Therapeutic Antibodies Against Shiga Toxins: Trends and Perspectives - Henrique, Izabella de Macedo; Sacerdoti, Flavia; Ferreira, Raissa Lozzardo; Henrique, Camila; Amaral, Maria Marta; Piazza, Roxane Maria Fontes; Luz, Daniela (Frontiers in Cellular and Infection Microbiology, 2022)
Shiga toxins (Stx) are AB5-type toxins, composed of five B subunits which bind to Gb3 host cell receptors and an active A subunit, whose action on the ribosome leads to protein synthesis suppression. The two Stx types (Stx1 and Stx2) and their subtypes can be produced by Shiga toxin-producing Escherichia coli strains and some Shigella spp. These bacteria colonize the colon and induce diarrhea that may progress to hemorrhagic colitis and in the most severe cases, to hemolytic uremic syndrome, which could lead to death. Since the use of antibiotics in these infections is a topic of great controversy, the treatment remains supportive and there are no specific therapies to ameliorate the course. Therefore, there is an open window for Stx neutralization employing antibodies, which are versatile molecules. Indeed, polyclonal, monoclonal, and recombinant antibodies have been raised and tested in vitro and in vivo assays, showing differences in their neutralizing ability against deleterious effects of Stx. These molecules are in different phases of development for which we decide to present herein an updated report of these antibody molecules, their source, advantages, and disadvantages of the promising ones, as well as the challenges faced until reaching their applicability.